SHIFT IN PARADIGM: STARTUP BUSINESS-INCUBATION AT UNIVERSITIES DURING THE EDUCATIONAL DISCIPLINE INSIDE OF CURRICULUM RATHER THAN EXTRACURRICULAR ACTIVITIES OF STUDENTS - Popov, Vladimir (Scientific Journal of Astana IT University, 2022)
Diploma or Dropout - it is argued, whether graduation is more important than a successful startup. Students drop either college or their ideas. A presented exploratory study about the incubation of technological startups among students tries to solve this contradiction. The curricula business incubation as the educational discipline inside of the curriculum was offered in opposition to the extracurricular activities of students. There is not a lot of data about this model of student incubation outside of the university’s entrepreneurship center and every contribution is valuable. The used research method is Qualitative studies, so the surveys among students are conducted during and after the incubation process on the educational discipline "Startup & Technological Entrepreneurship". At the end of this research, the framework was proposed, a set of actions, for helping students to go all the way from Idea to Product and Techno-Business. The framework is tested on a limited number of students in several universities in developing countries. The experiment is about embedding the syllabus into the Curriculum and measuring of achievements of students. The course is supposed to be elective and only students wishing to develop something are accepted. Later, interviews are conducted with two groups of students: those who passed the offered course and those who tried to develop startups independently. The final aim is to prove whether the inter-curricular framework works and how it overperforms other similar extra-curricular solutions.